Design and Output Power Evaluation for a Novel Hybrid Wave-Wind Energy Converter - Khaleghi, S; Lie, TT; Baguley, C (Elsevier BV, 2022)
The performance of oscillating water column (OWC) wave energy converters (WEC) is highly affected by airflow rate. In this paper, a novel system is proposed that increases airflow rate and, therefore, output power through the integration of a mechanical structure known as a windcatcher with a conventional OWC. To investigate the hydrodynamic behaviour of the proposed system, a non-linear two-dimensional computational fluid dynamics (CFD) model is employed, along with the Reynolds Averaged Navier-Stokes (RANS) approach. The results of a comparison of the proposed OWC to a conventional type reveal a significant increase in airflow rate through the turbine blades, realizing an increase in converter output power. Moreover, the results show a power generation consistency in the proposed hybrid system, as the amplitude of the oscillatory part of the turbine airflow rate is diminished. Therefore, the proposed OWC converter not only generates significantly more power than a conventional type, it also has smoother power generation performance.
Keywords: Wave energy converter; Oscillating water column; Windcatcher; CFDRANS